Горение древесной пылевоздушной смеси в цилиндрическом канале - Ignatenko Д.; Mironov В.; Penyaz’kov О.; Skilond’ А. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2012)
The setup for studying the propagation and acceleration of two-phase flames with automatic control based on controller, pneumatic valves and high-current relays is described. Front combustion and acceleration velocities as a function of time, as well as distributions of the above velocities and combustion front accelerations with working channel height for wood dust of two fractions: from 50 to 100 micrometers and less than 50 micrometers are obtained. The length of the working section is 0.5 and 1.0 m. The dependences of excess pressure in the working channel and a rate of its rise for combustion of rich dust-air mixtures are presented here. The combustion behavior and its characteristics with different stoichiometry coefficients are analyzed. The results obtained can be used to construct and test combustion models in heterogeneous systems.